Racialization and Aporophobia: Intersecting Discriminations in the Experiences of Non-Western Migrants and Spanish Roma - Zenia Hellgren; Lorenzo Gabrielli (Social Sciences, 2021)
In this article, we address a gap in the scholarship on (super)diversity, discrimination and racism by placing the experiences of non-western migrants and Roma people in the same conceptual framework of stigmatization based on racialization and aporophobia. Including a (formally non-recognized) national minority, the Spanish Roma, in such an analysis implies moving from a framework of superdiversity applied to immigrants to a broader one, which also applies the notion of superdiversity to the racialized citizens of a country, shifting the focus from inner-group features to exogenous othering processes by the mainstream society. We aim to also contribute to the literature on the race–class binary with our empirically grounded analysis of how racialization and aporophobia intersect in the negative stereotyping of people who are cast as outsiders based on both their race/ethnicity and (assumed) socio-economic status. Data from several different research projects on migrant and Roma inclusion/exclusion in Spain were used for the analysis, which focuses on the intersections between race and class in the narratives on exclusion and discrimination by 185 migrant and Roma men and women that were interviewed between 2004 and 2021. The analysis shows that our Roma and migrant respondents perceive forms of discrimination based on racialization and aporophobia that are similar in several ways. In turn, the “double stigmatization” experienced by many of our respondents reinforces their actual precariousness, which may be understood both as a cause and consequence of this stigmatization. We found that these experiences were salient in the narratives of both non-western migrant and Roma respondents who find themselves part of a “racialized underclass” and struggle with finding ways to exit the vicious circle of devalued identities and material deprivation.